The efficacy of topical baclofen 5% on posthemorrhoidectomy pain : A randomized double blind placebo controlled clinical trial - Mansourifar, Mohaddeseh; Ala, Shahram (International Pharmacy Acta, 2018)
Background : baclofen is gamma-amino butyric acid (GABA) agonist is an inhibitory neurotransmitter in the mammalian nervous system and is also found in peripheral tissue including lung. It is also used in muscle spacity and cerebral spacity . in this study the efficacy of baclofen cream 5 % in reducing postoperative pain during defecation after hemorrhoidectomy was investigated. Introduction: A total of 66 patient with third and fourth degree hemorrhoids open hemorrhoidectomy were included in this prospective double blind randomized controlled trial. The patients were randomly assigned to either baclofen cream or placebo immediately after surgery and then every 12 h for 14days. The primary outcomes were intensity of pain during defecation, measured with a visual analog scale. Methods and Results: there was no significant difference in the average postoperative pain score in the first 48 h ( P24= 0.3 , P48= 0.5 ) after the surgery between the two groups, but at week 1 the pain score during defecation were considerably lower in the baclofen group than in placebo group ( P=0.01) , which also was the same at the week 2 (P=0.02) . there was no significant difference in the average acetaminophen administration at 24 , 48 h between 2 group after surgery, but Acetaminophen requirement after week1 and week 2 in baclofen group significant lower than placebo ( Pweek1= .025 Pweek2 = .024 ) Conclusions: . compared with baclofen cream and placebo reduced postoperative pain and painkiller requirment during defecation .